The impact of clinical and laboratory parameters on clinical pregnancy and live birth rates in fresh cycles: a retrospective study of 9608 high-quality cleavage-stage embryos - Haijing Zhao; Keer Gan; Xiaohui Ji; Lingyan Zheng; Songbang Ou; Mei Mei; Qingxue Zhang; Hui Chen; Ping Yuan; Wenjun Wang (Journal of Ovarian Research, 2024)
Abstract Background Evidence from the Istanbul consensus workshop suggests correlations between morphological parameters and embryo developments. 8-cell embryos are the best blastomere stage on day 3. No good quality evidence exists to support high-quality embryonic selection following blastulation and clinical outcomes. This study aimed to investigate the factors that affect blastocyst formation, blastocyst quality, and clinical outcomes of high-quality cleavage-stage embryos in fresh cycles. Methods This study was a retrospective analysis of 9608 high-quality cleavage-stage embryos from 2987 couples between January 2017 to June 2021, namely 1520 embryos categorized as “812” (8-cell, grade 2, mild fragmentation), 2961 as “821” (8-cell, grade 2, mild asymmetry), 896 as “711” (7-cell, grade 1), and 517 as “911” (9-cell, grade 1) compared with 3714 embryos categorized as “811” (8-cell, grade 1). The primary outcomes were clinical pregnancy rate (CPR) and live birth rate (LBR). Blastulation rate (BR), available late blastocyst rate (ABR) and high-quality late blastocyst rate (HBR) were secondary outcome measures. Results BR, ABR, and HBR had significant differences among the five groups (P < 0.001), while CPR and LBR were also significantly different in cleavage-stage fresh transfer (P < 0.01). The multivariable multilevel logistic regression analysis revealed a significant association between cell number, cell size, blastocyst development and clinical outcomes. For 7 to 9-cell highest-quality embryo, mild fragmentation and more blastomeres were more conducive to blastocyst formation and clinical outcomes. While cleavage-stage embryos developed into blastocysts, the negative impact of their initial morphology on clinical outcomes would be erased. Conclusions Our study firstly evaluated blastocyst development and clinical outcomes of high-quality cleavage-stage embryos in fresh cycles, with rankings of 811, 812, 911, 821, and 711. We found the initial morphological characteristics of the high-quality cleavage-stage embryos did not adversely impact clinical outcomes, even as they progressed to the blastocyst stage.